From “boat to plate”: creating value through sustainable fish supply chain visibility - Duarte de Almeida, I. (2016)
Environmental concerns about the scarcity of marine resources are critical driving forces for firms aiming to prepare their supply chains for sustainability. Building on previous work, this paper highlights the mplementation of good practices geared towards sustainable operations in the seafood department, which were pursued in an exploratory retailer case. Outcomes of the adopted environmentally and socially acceptable fish retailing strategies, ranged from traceability, to self-certification and eco-labelling. The consequences for business were, as follows: stronger collaboration and trust across the chain of custody, improvement of sponsors’ image and of consumers’ loyalty and, progress in the Greenpeace retailers’ evaluation ranking.